Long-term retrogradation properties of rice starch modified with transglucosidase. (December 2021) - Li, Jiahao; Zou, Feixue; Gui, Yifan; Guo, Li; Wang, Na; Liu, Pengfei; Cui, Bo
Abstract: The retrogradation properties of rice starch (RS) treated with transglucosidase (TG) were investigated. The degree of branching (DB) increased from 12.26 to 15.16% with increasing TG treatment time except for 20 h. The relative crystalline of the retrograded TG-treated starches decreased from 26.44 to 21.57% with increasing DB. While the crystalline peak intensity became narrower and sharpener due to the formation of a much more uniform crystal structure, hence resulting in a lower mobility of water. Also, the spin-spin relaxation time (T2) decreased with increasing DB. The T22 and T23 significantly decreased by 80.47 and 64.46%, respectively. The Avrami kinetics demonstrated that the retrogradation rate of rice starch was retarded due to the decrease of rate constant k after TG treatment. The study may provide a promising theoretical basis on retarding retrogradation of rice starch to improve the qualities and extend shelf life of the rice staple foods. Graphical abstract: Image 1 Highlights: Rice starch was modified with transglucosidase to increase the branching degree (DB). The DB values of rice starches increased with increasing TG treatment time (<20 h). The crystallinity of retrograded TG-treated starches decreased, but peak intensity became stronger. The spin-spin relaxation time (T2 ) of retrograded TG-treated starches decreased with increasing DB. TG treatment resulted in a decrease of the retrogradation rate constant ( k ).